2009
DOI: 10.1016/j.joen.2009.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Using Diazotization to Characterize the Effect of Heat or Sodium Hypochlorite on 2.0% Chlorhexidine

Abstract: Introduction: The combination of sodium hypochlorite (NaOCl) and chlorhexidine (CHX) results in the formation of a precipitate. In a previous study, we demonstrated the formation of 4-chloraniline (PCA) in the precipitate in an amount directly related to the concentration of NaOCl used. Aims and Methods: The aim of the present study was to use a diazotization technique to confirm the presence of an aromatic amine (like PCA) in the NaOCl/CHX precipitate and also in the 2.0% CHX at different temperatures (37 C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
(45 reference statements)
0
26
0
2
Order By: Relevance
“…At the same time, NaOCl molecules are consumed, resulting in a decrease concentration and local activity (14) . Several studies have analyzed the interaction between NaOCl and CHX and found mixed results; while some have ruled out the presence of PCA (8,15) , others have demonstrated the formation of a brown-orange precipitate when NaOCl and CHX solutions are mixed, in addition to the presence of PCA in the precipitate (7,(16)(17)(18)(19) . These differences could be due to the varied methodologies used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, NaOCl molecules are consumed, resulting in a decrease concentration and local activity (14) . Several studies have analyzed the interaction between NaOCl and CHX and found mixed results; while some have ruled out the presence of PCA (8,15) , others have demonstrated the formation of a brown-orange precipitate when NaOCl and CHX solutions are mixed, in addition to the presence of PCA in the precipitate (7,(16)(17)(18)(19) . These differences could be due to the varied methodologies used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…These fi ndings might be clinically relevant because PCA has been shown to be toxic. Considering that CHX can break down to form PCA by exposure to heat, it is not recommended to elevate the temperature of the CHX [ 8 ]. Figure 5.11 shows that the end products of the PCA, NaOCl/CHX precipitate, and 2.0 % CHX at 45 °C were yellow, indicating that an aromatic amine was present in all samples.…”
Section: Chx + Heatmentioning
confidence: 99%
“…MTAD has been recommended in clinical practice as a fi nal rinse after completion of conventional chemomechanical preparation [ 75 , 89 , 91 ]. Tubes with PCA and the NaOCl/CHX precipitate turned yellow after heating them to 45°, indicating that the amine (PCA) was present [ 8 ] Tetraclean (Ogna Laboratori Farmaceutici, Muggio, Italy) is a combination product similar to MTAD. The two irrigants differ in the concentration of antibiotics (doxycycline 150 mg/5 ml for MTAD and 50 mg/5 ml for Tetraclean) and the kind of detergent (Tween 80 for MTAD, polypropylene glycol for Tetraclean).…”
Section: Biopure Mtad and Tetracleanmentioning
confidence: 99%
“…It is interesting that chlorhexidine used in combination with 3% hydrogen peroxide is more effective in combating E. faecalis bacteria than the independent use of both of these two fluids [20]. It is, however, inadvisable to use chlorhexidine as a rinsing agent immediately after NaOCI, as there is a chemical reaction which takes place between them, leading to the formation of a precipitate containing para-chloroaniline (PCA) [21][22][23]. PCA is highly toxic and is potentially carcinogenic, which has been observed in animal tests [24].…”
Section: Chlorhexidine -Chxmentioning
confidence: 99%